Toys Wonderland / Dyg Arwinna Haszlin Abg Sulaiman ... [et. al] - Abg Sulaiman, Dyg Arwinna Haszlin; Apandi, Nurfatini; Bundan, Angeline Entang; Azamri, Nur Azmeera; Adenan, Muhammad Annwar; Salleh, Mohammad Danial (2012)
Toys Wonderland is a partnership business in form of business which consist of six shareholders. All shareholders have agreed stated in agreement letter which consist the amount of capital, and the profit and loss will be divided as stated ratio. We had chosen this kind of business because it shows the equality and no one will discriminate, as the profits and losses are equally divided in the end of the accounting period. In other ways, the partnership is a perfect option to be taken because the shareholders will always share ideas and knowledge in order to gain profit and achieve high productivity time to time. We also offer a great deal of playing games and toys.